Perilaku Kepemimpinan Kepala Sekolah Dalam Meningkatkan Motivasi Kerja Guru Di SMP Negeri 1 Wera - Nanang Sugiharti; A. Hari Witono; Radiusman Radiusman; Lalu Sirajul Hadi (Magister Pendidikan Dasar FKIP Universitas Mataram, 2025)
In the world of education, a leader is required to be able to provide motivation to teachers/education personnel so that they have the enthusiasm to carry out their duties in order to educate the nation's children in accordance with the national education goals stated in the 1945 Constitution. These goals can be achieved, if in a teacher's learning process has intrinsic motivation. The principal should be able to provide external motivation that can encourage teachers to work seriously. The aim of the research is to determine the leadership behavior of the Principal towards teacher work motivation. The method used is a qualitative descriptive technique, then data is collected through a field survey by creating an instrument on the Google Form application. The research period was carried out from March-April 2024. The research results showed that the respondents who responded consisted of 81.4% women and 8.6% men. Based on the survey results regarding the instrument, a pleasant boss can encourage oneself to work well, getting the highest response, namely 79.5%. Then a conducive work environment, availability of facilities and infrastructure to motivate oneself, received the second highest response, namely 79.1%. This means that a pleasant boss and a conducive work environment have a very strong influence in increasing teacher work motivation. Meanwhile, the influence of incentives/honorariums had varying responses from very strong (49.9%), this means that almost 50% of respondents stated that honorariums could influence the emergence of very strong motivation within themselves. As many as 29.5% stated that they had a strong influence, meaning honorariums/ Incentives also have a strong influence on generating self-motivation. There are variations in responses to the influence of honorariums because each individual has a different response when given incentives, because each individual has different financial levels and needs. Conclusion: A conducive work environment, availability of facilities and infrastructure can increase self-motivation, which has a very strong influence among other survey results, namely 79.1%. Another factor that can influence teacher work motivation besides a conducive work environment is honorarium/incentives.